The impact of chief risk officer appointments on firm risk and operational efficiency. Issue 3 (16th March 2022) - Li, Huashan; Lam, Hugo K. S.; Ho, William; Yeung, Andy C. L.
Abstract: To exercise risk control at the corporate level, firms often appoint Chief Risk Officers (CROs) to their top management team. By establishing CRO positions, firms can reduce firm risk and potential financial losses caused by operational disruptions. Yet, by inducing stringent control measures on risks, security, and compliance, CRO appointments might create unwieldy bureaucracies with operational hurdles and incur burdensome costs that offset efficiency. Using longitudinal secondary data collected from multiple sources, we analyze the impact of CRO appointments on firm risk and operational efficiency of 435 publicly listed firms in the United States from 2006 to 2016. Our results indicate that CRO appointments not only reduce risks, but also improve efficiency in operations. We delve into the power of CROs and find that more powerful CROs are more effective in enhancing the operational efficiency of firms. We further examine the contextual factors and reveal that firms operating under high industry litigation threats and industry dynamism improve operational efficiency to a greater extent after CRO appointments. Overall, CROs' appointments are more beneficial to firms when they have stronger power in the top management team and when the operating environments are uncertain and volatile. Highlights: Chief Risk Officer (CRO) appointments help reduce firm risk and improve operational efficiency. The performance impact of CRO appointments is more pronounced when the appointed CROs have stronger power. Firms operating in litigious and dynamic environments benefit more from CRO appointments.